A Study of Compressive Strength Characteristics of Laterite Sand Hollow Blocks - Olugbenga Ata; Kolapo Olusola; Oludare Omojola; Abiodun Olanipekun (Civil Engineering Dimension, 2007)
This paper presents the results of experimental investigations carried out on partial replacement of sand with laterite as it affects the compressive strength of sandcrete hollow blocks. Two mix proportions (1:6 and 1:8) were used with laterite content varying between 0 and 50% at 10% intervals. Hand and machine compaction methods were used. Curing was done by sprinkling water on the specimens. The results showed that for each mix proportion and compaction method, the compressive strength decreases with increase in laterite content. Machine compacted hollow sandcrete blocks made from mix ratio 1:6 and with up to 10% laterite content is found suitable and hence recommended for building construction having attained a 28-day compressive strength of 2.07N/mm2 as required by the Nigerian Standards.